Cycloferon as a Means for Prevention, Treatment, and Control of COVID-19: Multidisciplinary and Comparative Historical Aspects - P. V. MAZIN; R. K. KHAFISIANOVA; V. P. MAZIN; A. A. GALKIN; A. K. OSKANOV (Антибиотики и Химиотерапия)
The study of coronaviruses, including those capable of causing life-threatening diseases, continued for many decades. So did the study of interferons, as well as acridine acetic acid, which is a powerful interferon inducer. For a long time, both directions of research developed in parallel to each other. However, the discovery of SARS-CoV and the creation of Cycloferon based on acridine acetic acid made both research directions converge. To date, the abundance of factual and theoretical tenets is enough to estimate the potential effectiveness of acridine acetic acid against COVID-19.